Investigasi Forensik Konduktivitas Listrik Mikro Bead Tembaga Sebagai Upaya Mengidentifikasi Penyebab Kebakaran - Riyanto, Sulistiana Agung; Ferdian, Deni (Jurnal Mesin Nusantara, 2023)
The purpose of this study was to evaluate the characteristics of the bead formed due to short circuit, overload and direct flame treatment on NYM 3x1.5 copper power cable. Handling of short circuit and overload is carried out at a current load of 800% of the current carrying capacity (144 Amperes) and direct flame treatment is carried out at a temperature of 960 degrees Celsius. The bead specimens formed from each treatment were examined and tested in the laboratory: chemical composition examination, visual inspection, macro and micro structural examination, hardness testing, and SEM-EDS examination. The difference in the characteristics of the arc bead that is formed under short circuit conditions and overload is that in short circuit conditions the damage point is localized at a certain point, namely at the short circuit contact point, while under overload conditions the point damage is localized at one or several specific locations along the wire. The macro characteristic of arc beads formed under short-circuit and overload conditions is that they contain many cavities and a clear transition boundary between the melted/ re-solidified material and the non-melted material. While the characteristics of the granules in the form of globular formed in the direct flame treatment, do not show sharp transitions between melting/ re-solidified materials. The micro structure of NYM 3x1.5 beads of electrically conducting copper wire material under the treatment conditions: short circuit, overload and direct ignition, is an alpha (α) phase dendritic structure.